2013
DOI: 10.2146/ajhp120221
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist management of patients with diabetes mellitus enrolled in a rural free clinic

Abstract: Pharmacist management of patients with type 2 diabetes significantly influenced clinical and economic outcomes in an uninsured population living in a rural area with few health care resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 15 publications
2
44
0
Order By: Relevance
“…Pharmacist-led free clinics has been shown to provide significant reductions from baseline in HbA1c values, systolic blood pressure, and triglyceride levels, which equates to health-care savings of $1,118 per patient who had a decrease of >1% in HbA(1c) value 8. Our study is in line with this notion.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Pharmacist-led free clinics has been shown to provide significant reductions from baseline in HbA1c values, systolic blood pressure, and triglyceride levels, which equates to health-care savings of $1,118 per patient who had a decrease of >1% in HbA(1c) value 8. Our study is in line with this notion.…”
Section: Discussionsupporting
confidence: 82%
“…The increase in hospital use could be attributed to increased distance to clinics, lack of adequate transportation, relative shortage of specialists and diabetes educators, cultural beliefs, and patient cost of care 5,6. It has been demonstrated that pharmacist-led free clinics in rural areas that provide educational programs to diabetic patients result in significant patient outcome improvements and financial savings 8. The current study focuses on painful diabetic neuropathy (pDN) in a rural diabetic population of South Carolina that is assisted by a pharmacist-led diabetes self-management education and support (DSEM/S) program.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, 19 were conducted in the USA [5][6][7][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], while each of the remaining studies was conducted in a different country: the UK [34], Bulgaria [35], Canada [36], Australia [37], Colombia [38] and Brazil [39]. Most of the studies were conducted in a community pharmacy (n = 10) [5,6,20,25,[28][29][30][35][36][37], or a clinic or hospitalbased outpatient facility (n = 8) [18,21,24,27,[31][32][33][34]. Two studies enrolled participants from various practice settings [7,22], while the remaining five studies did not delineate the practice settings [19,23,26,…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that patients who received pharmacist-managed care demonstrated improved A1c values. [7][8][9][10][11][12][13] Increased A1c is associated with increased costs per hospitalization, and these inpatient costs account for the major expenditure in health spending for patients with diabetes in the United States.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…[6][7][8] Previous studies have shown that patients with diabetes who receive clinical pharmacist interventions demonstrate significantly improved hemoglobin A1c. [7][8][9][10][11][12][13] Furthermore, the data have shown that increased A1c is associated with increased costs per hospitalization. In fact, patients with a mean A1c of at least 10% or greater have significantly higher rates of diabetes-related hospital utilization, compared with patients with a mean A1c of < 7%.…”
Section: Patient Selectionmentioning
confidence: 99%